S39 Human mesenchymal stem cells modulate alveolar macrophage polarisation In vivo and in vitro. (14th November 2013) - Morrison, T; McAuley, DF; O'Kane, C; Matthay, MA
Abstract : Rationale: ALI is characterised by dysregulated and excessive pulmonary inflammation. Macrophages are key cellular mediators of the lung innate immune response. It is recognised that macrophages can be polarised towards an M1 (implicated in driving inflammation and the development of ALI) or an M2 (responsible for the resolution of inflammation) phenotype. We have previously reported that bone marrow-derived mesenchymal stem cell (MSC) treatment is protective in several models of ALI. To effectively translate MSCs into clinical practice, a better understanding of the mechanisms mediating their effect is needed. The current studies were undertaken to test if human MSCs have a role in polarising alveolar macrophages towards an M2 phenotype In vivo and in vitro . Methods: In vivo studies were preformed using a mouse model of E.coli pneumonia. C57BL/6 mice were administered 10 6 CFU of E. coli intratracheally (IT), treatment with MSC was given IT 4 h later. BAL cytokine levels were measured by ELISA. For in vitro studies MSC and AM were co-cultured without cell contact, using a Transwell system. Expression of cell surfaceCD206 (mannose receptor, widely accepted to be a marker for M2 activation) and phagocytic activity were assessed by Flow Cytometry both In vivo and in vitro . Results: In the In vivo model of E.coli pneumonia, hMSC treatment demonstrated reduction in the severity of lung injury, improved bacterial clearance and reduced TNF-α levels in the BAL 24 h after infection, compare to PBS-treated animals. hMSC administration was associated with significant up-regulation of CD206 on AM (Figure 1 ). In addition, in vitro co-culture with hMSC markedly decreased LPS-induced TNF-α secretion by mouse AM, significantly up-regulated their expression of CD206 and enhanced their phagocytic activity towards bacteria. Interestingly, co-culture with MSC was associated with marked up-regulation of AM expression of CD11b and CD11c, both of which (among other functions) mediate bacterial phagocytosis. Conclusions: Bone marrow-derived hMSCs have the capacity to change the phenotype and functional properties of alveolar macrophages. hMSCs drive the polarisation of AMs towards a less inflammatory state but at the same time have the unique capacity to increase the capacity of AMs to phagocytose bacteria. Supported by NHLBI HL51854 (MAM)